2012
DOI: 10.1038/jcbfm.2012.84
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Intracranial Aneurysms: Role of Inflammation

Abstract: Intracranial aneurysms (IAs) linger as a potentially devastating clinical problem. Despite intense investigation, our understanding of the mechanisms leading to aneurysm development, progression and rupture remain incompletely defined. An accumulating body of evidence implicates inflammation as a critical contributor to aneurysm pathogenesis. Intracranial aneurysm formation and progression appear to result from endothelial dysfunction, a mounting inflammatory response, and vascular smooth muscle cell phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
418
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 442 publications
(444 citation statements)
references
References 141 publications
(161 reference statements)
7
418
1
2
Order By: Relevance
“…Well-established regional differences in SMC phenotype at the molecular level have been documented and previously little was known about SMC differentiation in the cerebral circulation. Although prior studies have found that cerebral vascular injury and ischemia may result in an inflammatory response 3,14 and accumulating evidence suggests SMC phenotypic modulation and inflammation may have a role in the pathogenesis of cerebral aneurysms, 8 potential mechanisms remain incompletely understood. The current study presents novel data demonstrating that TNF-a produces profound phenotypic modulation of cerebral SMCs characterized by decreased expression of SMC contractile genes and increased expression of pro-inflammatory, pro-matrix-remodeling genes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-established regional differences in SMC phenotype at the molecular level have been documented and previously little was known about SMC differentiation in the cerebral circulation. Although prior studies have found that cerebral vascular injury and ischemia may result in an inflammatory response 3,14 and accumulating evidence suggests SMC phenotypic modulation and inflammation may have a role in the pathogenesis of cerebral aneurysms, 8 potential mechanisms remain incompletely understood. The current study presents novel data demonstrating that TNF-a produces profound phenotypic modulation of cerebral SMCs characterized by decreased expression of SMC contractile genes and increased expression of pro-inflammatory, pro-matrix-remodeling genes in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…8 This phenotypic alteration is believed to be characterized by a decreased expression of contractile proteins and an increased expression of inflammatory mediators. Prior studies have found that in response to injury and ischemia, TNF-a and other proinflammatory mediators are upregulated in cerebral blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] There is a continuous balance between hemodynamic stress and the integrity of the vessel wall. [5] Upon the hemodynamic insult, this balance is perturbed, leading to vessel wall weakening. Dilation results, as extracellular matrix is degraded by increased levels of matrix metalloproteinases (MMP) compounded by concomitant apoptotic death of vascular smooth muscle cells (VSMCs).…”
Section: Pathogenesismentioning
confidence: 99%
“…The majority of evidence from intensive investigation has implicated a mounting inflammatory response during the aneurysm pathogenesis. [5,6] This data ultimately provides promising targets for in vivo molecular imaging and noninvasive IA therapeutics. This article will discuss inflammation as it pertains to IA pathogenesis, with a focus on the most recent investigation.…”
Section: Introductionmentioning
confidence: 99%